The pandemic as a catalyst for teacher and student well-being - Ončevska Ager, Elena (Oxford University Press (OUP), 2023)
Abstract This article reports on a well-being project in which I took part and which was supported by my institution, a university department supporting the development of prospective teachers and translators of English, but also of other foreign languages. The project was designed and run in response to the COVID-19 pandemic and has the potential to inspire other institutions or ELT professionals to consider organizing similar well-being support in their own contexts. I first outline the setting that gave rise to the project and the literature that informed it. I then describe its design and report on the benefits for teacher and student well-being, as evidenced by their engagement in the project. Finally, I reflect on the lessons learnt and the implications for practitioners elsewhere.